Enhancing organizational performance through organizational agility and innovation: a study of Dubai's public institutions - Albedwawi, Maryam Tayyeb Abdulla Mohammed (2025)
This study aims to examine the role of institutional agility and management innovation in developing and improving organizational performance in government institutions in Dubai. Indeed, institutional agility and transformative innovation are of great importance in achieving the aspirations of Dubai government in advancing the reality of organizational performance in government institutions. The problem of the study appears in the difficulties faced by government institutions in the Emirate of Dubai in keeping pace with the requirements of the large population diversity and the broad movement of non-citizens. This requires all the institutions to enjoy institutional agility and management innovation in achieving the best levels of management performance (planning, organizing, directing control). Questionnaires were created according to the guidelines from the previous works and modified to match the study conditions. The research involves all employees at government institutions in Dubai, with 306 collected samples out of 439 distributed questionnaire sets. There were two independent variables in this study: Institutional Agility (IA) and Administrative Innovation (AI), as well as four dependent variables representing different dimensions of organizational performance (OP) and administrative processes encompassing Planning (AP), Organizing (AO), Leading (AL), and Controlling (AC) within government institutions in Dubai. The results indicate that on average, respondents perceive the Administrative Innovation Variable (AI) is significant for the development and enhancement of organizational performance in government institutions in Dubai. This suggests positive perceptions among respondents towards this variable, reflecting their consensus on the crucial role of guidance in improving organizational performance. Similarly, the results indicate agreement among respondents regarding the role of Controlling (AC) in fostering and enhancing organizational performance in government institutions in Dubai. These collective findings underscore a high level of approval from the respondents, highlighting the importance of these factors in their overall satisfaction. Furthermore, these figures imply that the variables are reliable and consistent in measuring their intended aspects. The study recommends conducting similar studies using different methodology such as the qualitative approach, which may use additional variables that may not have been included in the current research.